Clinical and Genetic Factors of Thrombogenic Risk in Patients with Retinal Vein Occlusion - Zuhriddinovna, Jalalova Dilfuza; Aziza, Odilova (American Journal of Biology and Natural Sciences, 2025)
Retinal vein occlusion (RVO) is a significant cause of visual impairment worldwide. Its pathogenesis is multifactorial, involving both clinical and genetic risk factors. This study aimed to evaluate the association of thrombogenic genetic markers and clinical characteristics with the risk of RVO. A total of 120 patients with RVO and 100 age- and sex-matched controls were examined. Genetic testing focused on Factor V Leiden, prothrombin G20210A mutation, and MTHFR polymorphisms. Clinical evaluation included systemic conditions, laboratory parameters, and ophthalmologic findings. Results indicated that patients with RVO exhibited higher prevalence of hypertension, diabetes mellitus, and hyperlipidemia. Factor V Leiden mutation was significantly more frequent in the RVO group, while prothrombin and MTHFR polymorphisms also contributed to increased thrombogenic risk. These findings highlight the importance of combined clinical and genetic assessment in identifying patients at high risk of RVO and guiding preventive strategies. Retinal vein obstruction is a common retinal vascular disorder that can lead to severe visual impairment. Its occurrence is influenced by multiple determinants, including systemic health conditions and inherited prothrombotic variants. This investigation aimed to evaluate the relationship between hereditary coagulation anomalies and systemic features with the incidence of venous blockage in the retina. A total of 120 affected individuals and 100 matched healthy volunteers were analyzed. Laboratory procedures focused on detecting Factor V Leiden, prothrombin G20210A, and MTHFR gene variants. Clinical evaluation encompassed metabolic, cardiovascular, and ocular assessments. Findings revealed a substantial association of hypertension, impaired glucose tolerance, and dyslipidemia with retinal venous obstruction. Genetic analysis demonstrated an increased frequency of Factor V Leiden among patients, with prothrombin and MTHFR polymorphisms also contributing to heightened thrombotic susceptibility. These outcomes underline the significance of comprehensive clinical-genetic profiling for early recognition of at-risk subjects and the implementation of preventive measures.